FACTORS AFFECTING REPRODUCTIVE AND PRODUCTIVE EFFICIENCY OF NILI RAVI BUFFALOES (Bubablus Bubalis) IN PUNJAB, PAKISTAN - M. A. Yasir1; A. Sattar; M. Z. Tahir; M. Akhtar; M. Binyameen1and Hammad-ur-Rehman (Journal of Animal and Plant Sciences, 2020)
The data on Nili Ravi buffaloes kept at Buffalo Research Institute (BRI), Pattoki, District Kasur, Punjab Pakistan were collected from 2010 to 2018 to estimate the factors affecting the reproductive and productive traits of Nili Ravi buffaloes. The reproductive parameters including age at maturity, age at first conception, age at first calving, gestation length, service period, calving interval and number of services per conception were 1029.59 ± 20.60 days, 1065.33 ± 20.20 days, 1417.6 ± 21.66 days, 312.27 ± 8.03 days, 227.16 ± 4.98 days, 485.15 ± 3.80 days and 1.60 ± 0.02, respectively. The productive parameters including 305-day milk yield, lactation length and dry period were 2211.05 ± 20.06 liters, 266.94 ± 1.49 days and 279.47 ± 5.19 days, respectively. The statistical analysis for the comparison among different treatments ANOVA technique was employed using GLM procedures, a significant effect of year and season of birth on age at maturity, age at first conception and age at first calving was observed (P≤0.05). The year of calving, season of calving and parity significantly affected calving interval, service period, services per conception and 305-day milk yield (P≤0.05). It is concluded that improvement in performance of Nili Ravi buffaloes can be made by better management, nutrition and effective heat detection program. Improved management of heifers may reduce age at maturity and age at first calving. Culling on the basis of production performance may improve productivity of buffalo in future.
Keywords: Pakistan; Nili-Ravi Buffalo; productive traits; reproductive traits